2011
DOI: 10.1002/pssa.201001210
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer spectroscopy analysis of iron compounds in carboxylated multiwall carbon nanotubes and their ammonium salt

Abstract: Different forms of iron compounds embedded in non‐functionalized (as prepared) and functionalized multiwall carbon nanotubes (MWCNTs) were studied. Iron used to catalyze MWCNT synthesis can be found inside nanotubes and built‐in within their walls. Mössbauer spectroscopy was applied to study valence and spin states as well as magnetic ordering of the iron compounds. In the Mössbauer spectra of as prepared MWCNTs the Fe3C carbide provides the main contribution. The content of Fe3C decreases by about 20 and 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
7
16
0
Order By: Relevance
“…Most probably they are related to the Fe clusters, which contamination in the nonfunctionalized MWCNTs is about 10 times higher than in the chemically treated MWCNTs. Their distribution is comparable to that of the small structures observed in the TEM pictures .…”
Section: Resultssupporting
confidence: 76%
“…Most probably they are related to the Fe clusters, which contamination in the nonfunctionalized MWCNTs is about 10 times higher than in the chemically treated MWCNTs. Their distribution is comparable to that of the small structures observed in the TEM pictures .…”
Section: Resultssupporting
confidence: 76%
“…Moreover, a comparison of these data with the results described in Ref. 53 shows that temperature is also a very crucial parameter in the process of purification. When HNO 3 was used as an oxidant but at a temperature lower by about 20 °C fractions of γ‐Fe and Fe 2 O 3 particles were not detected at all 53.…”
Section: Resultssupporting
confidence: 58%
“…So far, it has been reported that the purification of contaminated CNTs could be achieved via the functionalization of carbon nanotubes [9]. Through this procedure, it is possible to cover the CNTs surface by various chemical groups such as: -OH, -COOH, COONH 4 , etc.…”
Section: Introductionmentioning
confidence: 99%